2016
DOI: 10.1155/2016/2752506
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Calcium Fluoride-Based Composite Materials

Abstract: Aim of the study was to evaluate mechanical properties of light-curing composite materials modified with the addition of calcium fluoride. The study used one experimental light-curing composite material (ECM) and one commercially available flowable light-curing composite material (FA) that were modified with 0.5–5.0 wt% anhydrous calcium fluoride. Morphology of the samples and uniformity of CaF2 distribution were analyzed using Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
4
9
1
Order By: Relevance
“…The antibacterial filler introduction had no statistically significant effect on DTS, although the mean value for the control group was the lowest. Those findings are in opposition to the results obtained by Łukomska-Szymańska et al [ 101 ], Diaz et al [ 102 ], and Sokołowski et al [ 103 ], where nonfunctionalized calcium fluoride microparticles, zinc oxide three-dimensional microstructures, nanosilver, and nanogold decreased the DTS values of modified composites.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The antibacterial filler introduction had no statistically significant effect on DTS, although the mean value for the control group was the lowest. Those findings are in opposition to the results obtained by Łukomska-Szymańska et al [ 101 ], Diaz et al [ 102 ], and Sokołowski et al [ 103 ], where nonfunctionalized calcium fluoride microparticles, zinc oxide three-dimensional microstructures, nanosilver, and nanogold decreased the DTS values of modified composites.…”
Section: Discussioncontrasting
confidence: 84%
“…Increasing antibacterial filler concentration caused a small but systematic lowering of microhardness. This is in opposition to some findings for commercially available materials, where higher filler content was correlated with higher microhardness [ 117 ], but is in accordance with some research, where introducing antibacterial additives decreased microhardness [ 44 , 101 , 111 ].…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, extracting the most active components from EOs and introducing them into dental products (e.g., restorative materials) composition might be promising line of research. The abundance literature reported that there is great need for development of dental materials with antibacterial properties [ 4 , 8 , 10 , 12 , 55 , 80 ]. The results of previous studies on antibacterial properties of dental materials seemed promising and suggested that introducing antimicrobial agents into the composition of dental materials might improve their antibacterial potential without deteriorating the physico-mechanical performance [ 8 , 12 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity of monomers, such as 12-methacryloyloxydodecylpyridinium bromide (MDPB), has been widely investigated [ 5 ]. Among antibacterial agents introduced into the composition of dental resin materials, most commonly described in the literature are nanoparticles, such as silver, gold, titanium dioxide, zinc oxide or calcium phosphate, as well as fluoride-containing filler and fluoride compounds [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Essential oils (EOs) could be promising alternative to contribute to the antimicrobial effect of resin composite materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation